Market and price analysis : - Dahl, Dale C (McGraw-Hill, 1977)
This book provides an understanding of the economic organization and operation of the food and fiber sector of the U. S. economy. It provides good treatment of agricultural price analysis. There are also a number of texts that consider the various dimensions of the marketing systemn for agricultural inputs, farm products, and processing and distribution activities.